2022
DOI: 10.1186/s41687-022-00501-7
|View full text |Cite
|
Sign up to set email alerts
|

Siblings’ life aspirations in the context of Duchenne muscular dystrophy: a mixed-methods case-control study

Abstract: Background The inevitable and progressive loss of independence in Duchenne Muscular Dystrophy (DMD) patients may have an impact on their siblings’ life aspirations. The present cross-sectional case-control study investigated how aspirations differed between brothers and sisters of people with DMD and a stratified comparison group of nationally representative children/adults. Methods A web-based survey was administered October through December 2020.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…These findings are consistent with previous studies on DMD (Read et al, 2011; Schwartz et al, 2022), which have shown that DMD can have both negative and positive impacts on other family members. These impacts include unequal parental attention and availability to siblings, as well as positive effects such as increased family cohesion, knowledge, and maturity in siblings.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with previous studies on DMD (Read et al, 2011; Schwartz et al, 2022), which have shown that DMD can have both negative and positive impacts on other family members. These impacts include unequal parental attention and availability to siblings, as well as positive effects such as increased family cohesion, knowledge, and maturity in siblings.…”
Section: Discussionsupporting
confidence: 93%